Peningkatan Kesejahteraan Peternak Kecil melalui Perbaikan Manajemen Reproduksi dan Kesehatan Kambing di Kota Kendari - Badaruddin, Rusli; Saili, Takdir; Bahtiar, Bahtiar; Prasanjaya, Putu Nara Kusuma; Kimestri, Asma Bio; Hakim, Muh. Haidir; Putri, Anindyaningrum Zainal; Ilahude, Meygi Caesarika Putri (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Small-scale goat farmers play a vital role in supplying animal protein in Indonesia but continue to face challenges in improving productivity and livelihood, particularly due to suboptimal reproductive and health management of their livestock. This study aims to assess the impact of improved reproductive and health management practices on the welfare of smallholder goat farmers. The methods employed included technical training, field mentoring, and evaluation of animal health conditions before and after intervention. The results showed that implementing proper reproductive management—such as heat cycle tracking, selection of superior bucks, and systematic disease prevention and treatment—led to increased birth rates and decreased kid mortality. Consequently, farmers’ income rose by an average of 25% within one production cycle. This study highlights the importance of an integrated approach to reproductive and health management as an effective strategy to sustainably enhance smallholder farmers’ welfare.